2020
DOI: 10.1158/2159-8290.cd-19-1485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical BRCA1/2 Reversion Analysis Identifies Hotspot Mutations and Predicted Neoantigens Associated with Therapy Resistance

Abstract: Reversion mutations in BRCA1 or BRCA2 are associated with resistance to PARP inhibitors and platinum. To better understand the nature of these mutations, we collated, codifi ed, and analyzed more than 300 reversions. This identifi ed reversion "hotspots" and "deserts" in regions encoding the N and C terminus, respectively, of BRCA2, suggesting that pathogenic mutations in these regions may be at higher or lower risk of reversion. Missense and splice-site pathogenic mutations in BRCA1/2 also appeared less likel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 77 publications
6
102
1
2
Order By: Relevance
“…58 Notwithstanding, BRCA reversions are the only confirmed mechanism of resistance identified in clinical samples and their exact prevalence will be better defined with the acquisition of more clinical data from patients progressing on platinum drugs or PARPi. Of note, while this work was under review, an article by Pettitt and colleagues 59 was published elsewhere reporting similar findings to ours.…”
Section: Discussionsupporting
confidence: 83%
“…58 Notwithstanding, BRCA reversions are the only confirmed mechanism of resistance identified in clinical samples and their exact prevalence will be better defined with the acquisition of more clinical data from patients progressing on platinum drugs or PARPi. Of note, while this work was under review, an article by Pettitt and colleagues 59 was published elsewhere reporting similar findings to ours.…”
Section: Discussionsupporting
confidence: 83%
“…The case presented also has clinical relevance regarding the uses of cfDNA analysis vs tumor profiling to detect BRCA2 reversion mutations in patients with prostate cancer. The lack of detection of our reversion mutation by Guardant360 may relate to its large size (228 bp) relative to the typical reversion mutation, which is <100 bp (Pettitt et al 2020). Although some groups recommend cfDNA analysis over tumor biopsy for detection of the full spectrum of tumor heterogeneity (Carneiro et al 2018), others have found that the assay has limitations in detecting clinically relevant alterations (including large somatic deletions) in a significant percentage of patients (Taavitsainen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This novel mutation could be considered a reversion mutation, if occurring in cis with the germline mutation. It has not been reported in the IRC Database of Reversion Mutations (https ://reversions.icr.ac.uk/), one of the largest of such databases (Pettitt et al 2020). Because BRCA2 allelic loss was not reported by MSK-IMPACT, we attempted to determine this by performing qualitative polymerase chain reaction (qPCR) and Sanger sequencing on microdissected tumor tissue (Fig.…”
Section: Germline and Somatic Genomic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a long-term follow-up study of a large number of BRCA1/2 ovarian cancer patients, the 5-yr disease-free interval treated with platinum drugs is only ∌15% (Jorge et al 2019). The major mode of verified therapy resistance is reversion of the mutated gene (Chen et al 2018), with approximately 300 reversion alleles reported thus far from 91 patients (Pettitt et al 2020). Although reversion to wild type can occur, most often a secondary mutation restores the reading frame from a primary truncation mutation.…”
Section: Discussionmentioning
confidence: 99%